Get your business buzzing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Beekeeping as a business R Jones. Copublication of the International Bee Research Association (IBRA) and the Commonwealth Fund for Technical Co-operation (CFTC). 1999. 70 pp. ISBN 0 85092 631 9. £10.99 18 (excluding postage) IBRA. 18 North Ro